2017
DOI: 10.15314/tsed.296702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Narcissism Levels of Students in the Faculty of Sports Sciences in Terms of Some Demographic Variables

Abstract: The purpose of this study is to find out the narcissism levels of the students in Faculty of Sports Sciences and to compare these in terms of some demographic variables. The sample of the study consists of a total of 180 students (66 females, 114 males) studying in three different departments of faculty of sports sciences (Physical Training and Sports Education, Sports Management and Coaching Education) who agreed to participate in the study voluntarily. In the study, Narcissistic Personality Inventory was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…In the study of the literature, it has been observed that several psycho-social researches have been conducted on athletes, trainers and managers interested in different branches by dealing with different variables (Riemer & Chelladurai, 1995;Summers & Russel , 1991;Maby, 1997;Garland & Barry, 1988;Gordon, 1998;Prapavessis, 1991;Doğan et al,2018;Koç and Ermiş, 2016;Kabadayı et al, 2017;Cavusoglu et al, 2017;Bostancı et al, 2017;Bayram et al, 2017;Keskin et al, 2016;Bostancı, 2014;Ermiş, 2019). Yet, psychological endurance researches on athletes are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of the literature, it has been observed that several psycho-social researches have been conducted on athletes, trainers and managers interested in different branches by dealing with different variables (Riemer & Chelladurai, 1995;Summers & Russel , 1991;Maby, 1997;Garland & Barry, 1988;Gordon, 1998;Prapavessis, 1991;Doğan et al,2018;Koç and Ermiş, 2016;Kabadayı et al, 2017;Cavusoglu et al, 2017;Bostancı et al, 2017;Bayram et al, 2017;Keskin et al, 2016;Bostancı, 2014;Ermiş, 2019). Yet, psychological endurance researches on athletes are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…The humility total scores of the students who are athletes and the scores of the sub-dimensions do not differ significantly according to the sports types. Cavusoglu et al (2017) also found that the level of narcissism did not differ significantly according to the sports branch. However, Vaughan et al (2019) were stated that individual athletes scored higher than team athletes on narcissism.…”
Section: Discussion and Resultsmentioning
confidence: 78%
“…On the one hand, Woodman and Hardy (2003) opined that self-confidence is more important to participants in individual sports than those in team sports. On the other hand, studies have found that team sports players have higher levels of self-confidence compared to players in individual sports (Cavusoglu et al, 2017;Kajbafnezhad et al, 2011;Radzi et al, 2013;Zeng, 2003). Kajbafnezhad et al (2011) reported that athletes in team sports had higher scores on the sources of sports confidence compared to athletes in individual sports.…”
Section: Introductionmentioning
confidence: 99%